THE POWER OF STORY TELLING IN TEACHING SPEAKING - Mu`tashim, Jundullah Faris; Syafi'i, Ahmad (Universitas Nusantara PGRI Kediri, 2018)
ABSTRACT In Indonesia, learning English language is needed. Indonesia as a develop country realize the important of speaking English. Therefore in Indonesia, English lesson also put in curriculum. The purpose of speaking English is challenging, but this is not easy thing. The students should face some problem in learn speaking. The activity inside the classroom is bored. So, the teacher try to find the alternative way. Storytelling is one of the method in teaching. Story telling is one of the teaching speaking media in English language education. This media will help teacher to deliver material. According Sundmark (2014) and Remi (2011), storytelling has potential means to increase children language skills.